Plugin for reconstructing Boolean models of signaling - Ashok, Pranav. (2013)
In today’s era of faster and powerful computers, the steep increase in high-throughput data needs computational tools capable of integrating data of various types and facilitating recognition of biologically meaningful patterns within them. Since the time when networks of protein-protein interaction were discovered, more than ten years ago, they have been analyzed mainly in their topological aspects. Recently, there have been suggestions of the functional models of these networks, varying from constraint-based ones to Boolean networks.